The use of electrical source imaging in targeting lesional mesial temporal epilepsy for radiosurgical treatment. Issue 4 (December 2014) - Del Felice, Alessandra; Foroni, Roberto; Manganotti, Paolo; Storti, Silvia F; Ricciardi, Giuseppe K; Bashat, Dafna Ben; Longhi, Michele; Meglio, Mario; Nicolato, Antonio
<x xml:space="preserve">Abstract</x> Gamma knife radiosurgery (GK‐RS) is a technique applied in selected cases of mesial‐temporal epilepsy, although still limited to centres with adequate instrumentation and expertise. Here, we report a case of radio surgery targeted with the aid of electrical source imaging that localizes the cortical area generating the scalp epileptic discharges. The patient, a 39‐year‐old male, presented with a right mesio‐temporal lesion; electrical source imaging localization partially overlapped with the lesional area but showed an important activation of the omolateral frontal area, concordant with the epileptic network. The patient underwent GK‐RS, with good neurosurgical and clinical results. A radiosurgical ellipsoidal treatment volume area of 2×2×2 cm3, located over the right temporo‐mesial region within a centre showing abnormal signal intensity, was considered. Seven months after treatment, the patient developed brain oedema that gradually resolved after one year. After three years of follow‐up, the patient was seizure‐free (Engel class I). Our very preliminary experience suggests that electrical source imaging appears to be a useful supporting tool for the definition of the radiosurgical treatment volume in selected patients with temporo‐mesial lesional epilepsy.